Serum 25-OH Vitamin D in relation to Bone Mineral Density and Bone Turnover - Nicola Napoli; Rocky Strollo; Delia Sprini; Ernesto Maddaloni; Giovam Battista Rini; Enrico Carmina (International Journal of Endocrinology)
It is unclear which vitamin D status is optimal for bone health. In this study, we aimed to assess cutoffs of 25-hydroxyvitamin D (25OHD) derived by the literature (20, 25, or 30 ng/mL) in relation to bone turnover and bone mineral density (BMD). Serum 25OHD, PTH, osteocalcin, bone alkaline phosphatase, and C-telopeptide were measured in 274 consecutive postmenopausal women. BMD of the lumbar spine (L1–L4) and of femoral neck were also evaluated. 50 patients had normal BMD, while 124 had osteopenia and 100 had osteoporosis. 37.6%, 56.2%, and 70.8% subjects had serum 25OHD lower than 20, 25, or 30 ng/mL, respectively. No differences in bone turnover markers were found when comparing patients with low 25OHD defined according to the different cutoffs. However, a cutoff of 25 ng/mL appeared to differentiate better than a cutoff of 30 ng/mL in those subjects with reduced femoral neck BMD. The PTH plateau occurred at 25OHD levels of 26–30 ng/mL. In conclusion, vitamin D deficiency is common in Sicilian postmenopausal women and it may be associated with low BMD and increased bone turnover markers. Further studies are needed to better define the right cutoff for normal vitamin D levels in postmenopausal women.